Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar - Darby, Michael (Zootaxa, 2017)
Erro gen. n. a new genus of Ptiliidae (Coleoptera) with the new species impiger sp. n. and angolensis sp. n. is described and figured based on material collected in Angola and Madagascar. Pending further work on the phylogeny of the Ptiliidae the new genus is placed in the subfamily Ptiliinae where it appears to occupy a place close to the tribe Discheramocephalini.